Optimization of formulations of metoprolol succinate tablets containing ofada rice starch acetate as tablet matrix for sustained release using response surface methodology (2016)
Background: Release-retarding polymers in matrix tablets play a vital role in controlling drug release from tablets. Objectives: To prepare metoprolol succinate tablets by direct compression using Ofada rice (Oryza glaberrima Steud) starch acetate, degree of substitution (DS) 2.22, as a matrix for sustained release. Materials and methods: The central composite design and response surface methodology were applied to evaluate the interactive effects of three variables: percent content of starch acetate (X1), compression pressure (X2) and compression time (X3), on tablet crushing strength, friability and dissolution time (t80). Results: Crushing strength was 90.0 to 140.50 N; Friability 0.05 to 0.90% and t80 5.75 to 11.50 h. X1 and X2 had significant effects on crushing strength and dissolution time (p < 0.0001). The interactions between X1 and X2 and those between X1 and X3 were significant on crushing strength and dissolution time, and on friability respectively (p < 0.0001). The correlation coefficients indicated that the regression model represented the experimental data well (R2 = 0.9971 and R2 (Adj) = 0.9944 for crushing strength; R2 = 0.9976 and R2 (Adj) = 0.9954 for friability; R2 = 0.9979 and R2 (Adj) = 0.9961 for t80). Optimized conditions for formulation of metoprolol succinate tablets were 60 %w/w Ofada starch acetate; 150 MNm-2 compression pressure and 60s compression time. Conclusion: Optimized formulations of metoprolol tablets containing Ofada starch acetate with good mechanical strength and prolonged dissolution can be obtained when process conditions are adjusted within the reported values.